(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article scientifically analyzes the significance of Uzbek classical music in enhancing the spiritual consciousness of the people in the past, its role as one of the leading factors in social progress, and the influence of musical culture on shaping the spiritual worldview of Central Asian peoples, along with its stages of development.